The Influence of Accounting Information System Digitalization and Financial Reporting on the Quality of MSMEs' Financial Reports in South Jakarta: The Moderating Role of Digital Literacy - Sahrul Ramadhan; Maria Suryaningsih; Usman Andrianto; Susi Susilawati; Rama Yuli; Panji Supriyadi (International Journal of Management Science and Information Technology, 2026)
This study aims to examine the influence of accounting information system digitalization (X₁) and financial reporting (X₂) on the quality of MSMEs’ financial reports (Y) in South Jakarta, with digital literacy (Z) serving as a moderating variable. MSMEs in Indonesia continue to face challenges related to the quality of financial records and the limited utilization of digital technologies, which may hinder the production of reliable financial reports. This study employed a quantitative approach using a survey method involving MSME owners and managers in South Jakarta. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software. The findings reveal that accounting information system digitalization has a positive but statistically insignificant effect on the quality of MSMEs’ financial reports. Similarly, financial reporting does not significantly influence financial report quality. Furthermore, digital literacy is not found to moderate the relationships between accounting information system digitalization, financial reporting, and the quality of financial reports. These findings suggest that digital transformation among MSMEs in South Jakarta remains at an early stage of adoption and that the effectiveness of financial digitalization depends not only on the availability of technology but also on accounting competencies, organizational readiness, internal control mechanisms, and the integration of digital systems into business processes. In addition, the study highlights the need for refining measurement instruments and expanding future research by incorporating additional determinants of financial reporting quality. This study contributes to the growing body of literature on MSME accounting and digital transformation while providing practical implications for policymakers in designing more effective digital empowerment strategies for MSMEs.